1998
DOI: 10.1002/(sici)1096-9861(19980928)399:3<289::aid-cne1>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic alteration in peptidergic expression within a stable neuronal population in lobster stomatogastric nervous system

Abstract: In the adult lobster, Homarus gammarus, the stomatogastric ganglion (STG) contains two well-defined motor pattern generating networks that receive numerous modulatory peptidergic inputs from anterior ganglia. We are studying the appearance of extrinsic peptidergic inputs to these networks during ontogenesis. Neuron counts indicate that as early as 20% of development (E20) the STG neuronal population is quantitatively established. By using immunocytochemical detection of 5-bromo-2'-deoxyuridine incorporation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
4

Year Published

1999
1999
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 89 publications
(100 reference statements)
2
41
1
4
Order By: Relevance
“…Moreover, central projection neurons play a key role in the ontogeny of STNS networks because their presence masks preexisting adultlike phenotypes (Le Feuvre et al, 1999). In addition, immunocytochemical characterization of these inputs has shown that modulatory substances appear gradually in the STG during embryonic development (Cournil et al, 1995;Fenelon et al, 1998aFenelon et al, , 1999Kilman et al, 1999). However, such results do not exclude that some projection neurons may reach their target networks without expressing their final neurotransmitter phenotype.…”
Section: Abstract: Central Pattern Generator; Development; Modulatormentioning
confidence: 55%
See 4 more Smart Citations
“…Moreover, central projection neurons play a key role in the ontogeny of STNS networks because their presence masks preexisting adultlike phenotypes (Le Feuvre et al, 1999). In addition, immunocytochemical characterization of these inputs has shown that modulatory substances appear gradually in the STG during embryonic development (Cournil et al, 1995;Fenelon et al, 1998aFenelon et al, , 1999Kilman et al, 1999). However, such results do not exclude that some projection neurons may reach their target networks without expressing their final neurotransmitter phenotype.…”
Section: Abstract: Central Pattern Generator; Development; Modulatormentioning
confidence: 55%
“…Neuromodulatory systems involved in the control of central pattern generators (CPGs) have been extensively studied in terms of neuronal population, neurotransmitter phenotype, and alteration of network activity. A large body of work has been devoted to the progressive developmental acquisition of projection neurons using retrograde dye migration (Cabana and Martin, 1984;van Mier and ten Donkelaar, 1984;Okado and Oppenheim, 1985;Kudo et al, 1993) and of neuromodulatory substances using immunocytochemistry (Senba et al, 1982;Commissiong, 1983;Sako et al, 1986;van Mier et al, 1986;Rajaofetra et al, 1989;Pindzola et al, 1990;Fenelon et al, 1998aFenelon et al, , 1999Kilman et al, 1999). Using these approaches, it has been concluded that progressive acquisition of neuromodulatory substances by a target network is associated with axonal ingrowth of descending neurons (Sako et al, 1986;van Mier et al, 1986;Pindzola et al, 1990).…”
Section: Abstract: Central Pattern Generator; Development; Modulatormentioning
confidence: 99%
See 3 more Smart Citations